Contemporary relevance of Islamic thought. 3rd ed. - Ushama, Thameem (IIUM Press, 2025)
This book analyzes selected key issues in Islamic thought and its contemporary relevance. It is an attempt to conform to the mission of the Department of Usul al-Din and Comparative Religion of the International Islamic University Malaysia, which is committed to the "Relevantisation" of Islamic heritage, in addition to the Islamicisation of Human Knowledge. The principal objective is to enable students, staff, and people to obtain a correct and proper understanding of Islamic thought and inspire them to present an Islamic worldview by applying the method of moderation (Wasatiyyah). This study falls within 14 chapters. It deals with the concept of Rahmatan Li'l Alamin, nationalism in the discourse of Contemporary Relevance of Muslim revivalists, the feminist discourse in the Muslim world, secularism in the discourse of Maulana Abdur Rahim, Muslim response to Western criticism of Prophet Muhammad (pbuh), Mawdudi's approaches to the Qur'anic exegesis, spiritual ethics and character building, new religious movements in Malaysia, which promote controversies and dissensions, the sovereignty of Allah in the Qur'an, Muhammad Iqbal's theory of Selfhood, the influence of Imam al-Ghazzali in the Malay World, the impact of Islam on the Malay language, Mawdudi's view of education; its relationship with Islamisation of Knowledge and Meherullah's socio-religious and political thought.